The Art and Science of Innovation Transdisciplinary Work, Learning and Transgression - White-Hancock, Lorraine (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book addresses how innovation is generated in transdisciplinary work and learning, focusing on the interface between art, science and technology. It considers innovation in a new way by drawing on ideas about transgression, largely from a feminist perspective. Three of five case studies examined involve Synapse artist-in-residence projects where artists worked in collaboration with scientists in their scientific organisations in Australia as a means of encouraging innovation. The remaining two cases examine innovation and transgression in the collaborative work of the prominent Australian artist Patricia Piccinini and in the German Bauhaus school. This book appeals to artists and scientists, workplace managers, policy makers, researchers and educators interested in STEM or STEAM education.
1. Introduction -- 2. Innovation in policy and arts contexts -- 3. Workplace learning for innovation -- 4. Investigating transdisciplinary learning and innovation -- 5. Workplace learning for innovation in the arts: The Bauhaus school -- 6. Transdisciplinary spaces of innovation -- 7. The culture-order that authorises innovation -- 8. 'Doing' transgression -- 9. Conclusion. .
Keywords: Education and state; Art -- Study and teaching; Business; Management science; Educational Policy and Politics; Creativity and Arts Education; Business and Management